If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 4 + x = 1 + 6 Combine like terms: 3 + 4 = 7 7 + x = 1 + 6 Combine like terms: 1 + 6 = 7 7 + x = 7 Add '-7' to each side of the equation. 7 + -7 + x = 7 + -7 Combine like terms: 7 + -7 = 0 0 + x = 7 + -7 x = 7 + -7 Combine like terms: 7 + -7 = 0 x = 0 Solving x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Simplifying x = 0
| 6(y-5)=z(10+3y) | | 5x+11y+1z=57.73 | | 15x+13=3x-19 | | X-5c=8 | | .75a+14=18 | | X-3/6=1 | | .75+14=18 | | -4=5m+6 | | -17e=-204 | | 2x-33=x+1 | | 15n^2-n-16=0 | | 75-n+10=60 | | 9n+5n=23 | | 50-n+20=38 | | 4x-8=144 | | 90+40+(6x+2)=180 | | 55-n+41=62 | | 8(36+r)r=12 | | 2y+2a-8y=5 | | 6xsquared+9x=0 | | 1-4r-5r=1 | | 0.4(60)= | | 48-n+10=34 | | 15c-7=53 | | 6xsquared+9=0 | | .9x-2.3x=3.8 | | 10-n+60=64 | | 16.2(-4.5x-3)=-85.05 | | -4v+23=5(v+1) | | ln(3x+3)=0 | | 3(x-1)+(x-6)= | | (X-24)+29=64 |